(untitled) (Proceedings of Southern Federal University. Philology, 2016)
Julia A. Kozarenko, Anna A. Motozhanets (Southern Federal University, Rostov-on-Don, Russian Federation) The article dwells on translating techniques in reference to grammatical means of reflecting protagonists’ speech characetristics in fictional discourse. The research is based on English-Russian translations. Grammatical markers of protagonists’ speech are viewed as one of the most essential means of creating a fictional character and hence, objectivating the author’s intention. Any cases of neutralization of the above-mentioned grammatical markers are considered to lead to a substantional loss of both factual information and emotionalappraisive component in the majority of cases. Thus, compensation strategies with regard to grammatical markers of speech are seen as indispensable. The basic methods of reseach include the method of comparative analysis of the original and translated texts coupled with the method of contextual analysis. The equivalence of compensation relating to grammatical means of protagonists’ speech characterictics in translated text is assessed; in cases of neutralizations of grammatical markers the reasonability of neutralization is analyzed and compensation strategies are worked out; the most effective techniques are specificated. Functional transformation on a par with stylistic compensation based on lexical transformations are viewed among the most effective translating techniques with regard to grammatical means of protagonists’ speech characteristics. Key words: protagonists’ speech characetristics, fictional discourse, neutralization, functional transformation, compensation. DOI: 10.18522/1995-0640-2016-4-109-115